1989
DOI: 10.1029/jc094ic04p04947
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wind on transport and circulation in Lake St. Clair

Abstract: A numerical circulation and transport model is used to simulate currents and trajectories in Lake St. Clair. Results from the model are compared to three different types of measurements, namely, (1) mean currents from an array of fixed current meters, (2) currents measured from a ship during seven synoptic surveys of the lake, and (3) trajectories of satellite‐tracked drifting buoys during four different experiments. The model is then used to predict the effects of storms on the residence time of water enterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 13 publications
7
23
2
Order By: Relevance
“…The movement of the modeled drifters was mostly driven by surface circulation and not directly by wind, contrary to results in Lake St. Clair (Schwab et al, 1989). Tracer concentrations at the intakes result primarily from wind forcing (wind-driven currents) in the Kingston Harbour, Kingston Basin, and North Channel; similar to contaminant dispersion from the Red River plume in Lake Winnipeg .…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The movement of the modeled drifters was mostly driven by surface circulation and not directly by wind, contrary to results in Lake St. Clair (Schwab et al, 1989). Tracer concentrations at the intakes result primarily from wind forcing (wind-driven currents) in the Kingston Harbour, Kingston Basin, and North Channel; similar to contaminant dispersion from the Red River plume in Lake Winnipeg .…”
Section: Discussioncontrasting
confidence: 56%
“…(2)) did not improve the error estimates significantly, as was observed by Schwab et al (1989) except for D1, D4 and D9 where it was a slightly better predictor of observed drifter velocities. This difference could be due to the inclusion of drifter properties (drag, inertia, mass) in ELCOM (Furnans et al, 2008), which was not the case for results seen in Lake St. Clair (Schwab et al, 1989) and also that D1, D4, D9 were released away from the shore and islands (Fig. 5).…”
Section: Drifterscontrasting
confidence: 35%
See 1 more Smart Citation
“…The first scenario in this study consists of simulating the hydrodynamics for Lake St. Clair for the period June 1 to November 1, 1985, as carried out in Schwab et al (1989). This hindcast allows for both a comparison of modeled currents in Lake St. Clair with field measurements taken during this period, as well as comparison with a previously run two-dimensional numerical model for the same period (Schwab et al, 1989).…”
Section: Hindcastmentioning
confidence: 99%
“…In particular, Schwab et al (1981Schwab et al ( , 1989) used a structured grid, twodimensional rigid lid model to simulate time-variable currents and trajectories using meteorological forcing conditions from 1985 and made comparisons to current meter and survey observations. In addition, other two-dimensional models simulated wave-current interaction on Lake St. Clair, in which field measurements were employed for model validation (Tsanis and Wu, 1990;Brissette et al, 1993).…”
Section: Introductionmentioning
confidence: 99%